SIAMIK Success Evaluation at Bali Tourism Polytechnic: DeLone-McLean Evidence and Development Recommendations - Ni Putu Kasih Sumariani; I Made Candiasa; Luh Joni Erawati Dewi (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
Academic information systems are essential for supporting integrated academic services in higher education. However, SIAMIK at Bali Tourism Polytechnic still faces issues related to system integration, interface interactivity, manual grade processing, and limited digital service integration. This study evaluates SIAMIK success using the DeLone and McLean Information System Success Model and formulates system development recommendations based on empirical findings. A quantitative survey was conducted involving 102 users consisting of management, lecturers, administrative staff, and students. Data were collected through questionnaires and analyzed using descriptive statistics and Partial Least Squares Structural Equation Modeling. The results show that system quality significantly affected user satisfaction (β = 0.324, p < 0.001), information quality had the strongest effect (β = 0.433, p < 0.001), and service quality also had a significant effect (β = 0.170, p = 0.039). User satisfaction significantly influenced net benefits (β = 0.724, p < 0.001). The model explained 67.2% of user satisfaction and 52.3% of net benefits, with strong predictive relevance (Q² = 0.843). Findings suggest that SIAMIK development should prioritize information completeness, responsive access, technical support assurance, and cross-system integration.